Tunable bandgaps in free/lock switchable foldable polyline-rod: an introduction of tunable phononic crystals independent of durable external factors. (30th October 2019) - Han, Lin; Zhang, Yan; Li, Xiao-Mei; Jiang, Lin-Hua; Chen, Da
Abstract: We introduce a new principle independent of durable external factors in designing tunable solid phononic crystals (PnCs), to manufacture low-energy, simple and reliable tunable PnC devices. The free/lock switchable foldable polyline-rod, which has the powerful folding capacity under external factors for bandgap tuning, and the self-fixed capacity after the removal of external factors for bandgap maintenance, is proposed as an example. From the dispersion relation computations and frequency response tests, the proposed structure without special material requirements or complex deformations, is confirmed to give wide predictable tunable bandgaps effectively targeting any in-plane excitations, without relying on durable external factors.